Determinants of Labor Productivity in Java Island 2020–2024 - Intan Ambarsari Sihaloho; Dedy Yuliawan (Citakonsultindo, 2026)
Java Island is the center of national economic activity, contributing around 57 percent of Indonesia's total GRDP and accommodating 56.8 percent of the national labor force, or more than 86 million people, yet labor productivity across its provinces still shows significant disparity, with DKI Jakarta consistently outperforming the other provinces. This study aims to analyze the effect of the Provincial Minimum Wage, the Human Development Index (HDI), and Foreign Direct Investment (FDI) as a proxy for technology on labor productivity in six provinces of Java Island during the 2020–2024 period. The study uses a quantitative approach with panel data comprising 30 observations, combining five years of time-series data and cross-sectional data from six provinces, namely DKI Jakarta, West Java, Central Java, DI Yogyakarta, East Java, and Banten. The estimation model was selected through the Chow Test and the Hausman Test, both of which indicated the Fixed Effect Model (FEM) as the best model, and all data were processed using EViews 13. The FEM estimation results show that Provincial Minimum Wage has a positive and significant effect on labor productivity. HDI has a negative and significant effect, indicating that improvements in human development quality have not been fully matched by competencies suited to labor market needs. Meanwhile, FDI has a positive and significant effect as a channel of technology transfer that improves production efficiency and labor productivity.